Microelectrode Measurements of the Activity Distribution in Nitrifying Bacterial Aggregates - de Beer, D. (1993)
Microelectrodes for ammonium, oxygen, nitrate, and pH were used to study nitrifying aggregates grown in a fluidized-bed reactor. Local reactant fluxes and distribution of microbial activity could be determined from the microprofiles. The interfacial fluxes of the reactants closely reflected the stoichiometry of bacterial nitrification. Both ammonium consumption and nitrate production were localized in the outer shells, with a thickness of approximately 100 to 120 μm, of the aggregates. Under conditions in which ammonium and oxygen penetrated the whole aggregate, nitrification was restricted to this zone; oxygen was consumed in the central parts of the aggregates as well, probably because of oxidation of dead biomass. A sudden increase of the oxygen concentration to saturation (pure oxygen) was inhibitory to nitrification. The pH profiles showed acidification in the aggregates, but not to an inhibitory level. The distribution of activity was determined by the penetration depth of oxygen during aggregate development in the reactor. Mass transfer was significantly limited by the boundary layer surrounding the aggregates. Microelectrode measurements showed that the thickness of this layer was correlated with the diffusion coefficient of the species. Determination of the distribution of nitrifying activity required the use of ammonium or nitrate microelectrodes, whereas the use of oxygen microelectrodes alone would lead to erroneous results.